Effect of dietary eucalyptol on stress markers, enzyme activities and immune indicators in serum and haematological characteristics of common carp (Cyprinus carpio) exposed to toxic concentration of ambient copper - Seyyed Morteza Hoseini (2018)
© 2018 John Wiley & Sons Ltd In the present study, protective effects of dietary eucalyptol were investigated against copper toxicity in common carp (Cyprinus carpio). The fish were fed with diets supplemented with 0 (control), 0.5% and 1% eucalyptol for 14 days before exposure to 0.25 mg/L ambient copper for 7 days. Blood samples were taken from the fish before and 1, 3 and 7 days after copper challenge. Before copper challenge, eucalyptol significantly decrease serum aspartate aminotransferase (AST) activity, but increase blood WBC, RBC, hematocrit and haemoglobin, serum lysozyme, total immunoglobulin (Ig) compared with the control. Copper exposure led to stress, tissue damage and immunosuppression. After the copper challenge, significant elevation in serum cortisol, glucose, alanine aminotransferase (ALT) and AST, but decrease in blood RBC and WBC, and serum lysozyme, complement (ACH50) and total immunoglobulin (Ig) was observed. Eucalyptol administration significantly mitigated the increase in serum cortisol, glucose, ALT and AST, and decrease in WBC, ACH50, lysozyme and total Ig. Dietary 1% eucalyptol had significantly higher protective effects than 0.5% in the case of serum AST, lysozyme, total Ig and ACH50. In conclusion, eucalyptol has beneficial health effects on common carp and enables to mitigate copper-induced stress, tissue damage, and immunosuppression. Eucalyptol at the dietary 1% level is recommended to protect common carp against adverse effects of copper toxicity.